Investigation of structural and electrical properties of Zirconium dioxide thin films deposited by reactive RF sputtering technique - Coskun, Burhan; Asar, Tarik; Akgul, Unal; Yildiz, Koksal; Atici, Yusuf (Taylor & Francis Ltd, 2016)
ZrO2 thin films with different thicknesses (400nm, 500nm, 600nm) were deposited by reactive RF magnetron sputtering technique, on n-type Silicon (100) substrate at 200 degrees C applying 125W power ratin`g. The micro structural properties of thin films were obtained by Scanning Electron Microscope and it was observed that the films were grown successfully in the form of big grains formed by the accumulation of small particles. It was seen that the size of grains changed with the increase of film thickness. Energy-dispersive X-Ray spectroscopy was used to determine the chemical compositions of samples. The crystal structures of ZrO2 samples were analyzed by X-ray diffraction technique. In addition, the Current-Voltage and Capacitance-Voltage measurements were completed to investigate the electrical properties of samples.
Keywords: ZrO2 thin films; reactive RF sputtering; microstructure